Alcatraz / 6. - Smith, Roland, 1951- (I, Q, 2014)
"After thwarting the ghost cell's chemical attack in Chicago, Q and his stepsister Angela arrive in San Francisco to continue their parents' concert tour. They find themselves helping Boone and the S.O.S. team in the final showdown with the ghost cell and its leader, Number One"--Provided by publisher.